Chemical Composition and Extraction of Micro Crystalline Cellulose from Outer Skin Isolated Coffee Husk. (13th December 2022) - Zeleke, Nehemiah Mengistu; Sinha, Devendra Kumar; Mengesha, Getinet Asrat
Abstract : Coffee husk (CH) is a sustainable and abundantly available cellulosic waste material. Its fiber consists of cellulose as the major structural part which leads to potential utilization for the manufacturing of microcrystalline cellulose (MCC) products that can be utilized for different industrial applications. In the present study, chemical composition of outer skin-isolated coffee husk was determined and sequential treatments of various untreated (UT) sample, ethanol—toluene treated sample through dewaxed (DW) treatment, sodium hydroxide (NaOH)—treated sample through alkali (AT) treatment, and sulfuric acid (H2 SO4 )—treated sample through bleaching (BL) treatment have been carried out. The Micro Crystalline Cellulose (MCC) has been extracted through hydrogen peroxide (H2 O2 ) after BL treatment. The BL treatment for MCC extraction process was conducted without chlorine and additional harsh acid treatment, respectively. The characterization of chemically treated samples was carried out to investigate their morphological, physico-chemistry, and thermal behavior through a scanning electron microscope (SEM), Fourier transform infrared—ray (FTIR), X-ray diffraction (XRD), thermo gravimetric analysis (TGA), and differential temperature analyzer (DTA). From the chemical composition analysis; the cellulose, hemicellulose, lignin, and extractive content were determined and its values were (52.9%), (12.5%), (24.3%), and (9.4%), respectively. In the morphological examination, the great untreated (UT) fiber sample was greatly reduced into a micro-sized BL sample, revealing that (from FTIR analysis) the lignin and hemicellulose contents were greatly removed during chemical treatments and the presence of a micro crystalline cellulose region with 54.7% yield. Also, the sample AT and BL showed the lowest amorphous region in X-RD due to the removal of hemicellulose and lignin. The highest crystallinity index has been determined for the BL sample, i.e., 89.9%. Additionally, the thermal analysis shows that the AT and BL sample has great thermal stability than other (UT and DW) samples at high temperature. Therefore, the outer skin separated coffee husk was prepared from agricultural waste was subjected to eco-friendly chemical treatments to yield MCC. Thus, the extracted MCC is expected to be reliable for replacing other plant materials for the production of crystalline nanomaterial and reinforcing constituent for the fabrication of bio composite.